Innovative smart box learning media for enhancing elementary students’ conceptual understanding of arithmetic operations - Ade Putri Arbiyanti; Kufita Rachman; Siti Raihani Vesya; Ni Putu Miranda Puteri (Universitas Sarjanawiyata Tamansiswa, 2025)
Concept understanding is important to build in students, one of which is through learning media that can accommodate student needs. This research aims to develop the Smart Box as a learning medium for the mathematical operations of multiplication and division that is feasible and practical. This research is a research and development (R&D) study using the 4-D model, which consists of the stages of define, design, develop, and disseminate. The sample for this research consists of 25 fourth-grade students from SD Negeri Jurugentong, selected using random sampling from the population of fourth-grade elementary school students. Data collection instruments included interview guidelines and questionnaires. Interview data were analyzed descriptively, while questionnaire data were analyzed using descriptive statistics. The feasibility of the Smart Box media received an average score of 4.4 or 87%, categorised as